Preservice teachers equitably attending to and interpreting multilingual students' mathematical thinking - Jensen, Jessica L.; Gallagher, Melissa A.; Scrivner, Shaimaa; Mitchell, Morgan Love (School science and mathematics, 2023)
Research indicates that teachers may hold biases against multilingual learners (MLs). However, there is limited research regarding how teachers notice MLs' mathematical thinking. Given the complexity of teacher noticing and multilinguality, the lead researchers developed the Equitably Attending to and Interpreting a Student's Mathematical Thinking (EAST) framework to support preservice teachers' development of equitable noticing skills. Using a pre‐ and post‐intervention study design and EAST based lessons, we explored differences in preservice teachers' equitable noticing of MLs' mathematical thinking. We collected data on a noticing assessment from two groups of preservice teachers, 21 of whom received the EAST lessons, and 39 of whom received lessons on eliciting and interpreting student thinking without a focus on equity. Preservice teachers in both groups noticed components of the EAST framework, but more often noticed issues of access and achievement, and rarely attended to issues of identity or power. Findings from the study provide insight into what equitable noticing of a MLs' mathematical thinking entails, as well as areas for further development in both teaching and research regarding equitable noticing.